POTENSI DAN PERKEMBANGAN SUMBER DAYA PENGHIDUPAN (LIVELIHOOD RESOURCE) MASYARAKAT PERTANIAN DI WILAYAH PESISIR KECAMATAN KASEMEN KOTA SERANG BANTEN - Mirajiani, Mirajiani (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
Coastal areas are usually identified with the potential and development of economic sectors in the field of marine and fisheries. This is in line with the availability of livelihood resources associated with the sector. It is unique in the coastal area of Banten Province, especially the coastal area of Serang City, Banten which also has potential for economic development in the agricultural sector. This paper examines the extent to which the potential and development of agriculture and livelihoods of agricultural communities play an important role in the economy as well as explaining how the prospects for agricultural sector development in the region. The study method used a quantitative approach with the techniques of collecting and analyzing secondary data. The analysis is presented descriptively. This study shows that viewed from the livelihood resources of the agricultural community include physical capital (pshycal capital) and natural capital capital, then the agricultural sector is still potential and prospective in the coastal area of Kasemen district, Serang City. Potentials include the availability of agricultural land, appropriate geographical conditions, agricultural labor is still relatively high and the market potential is growing due to the development of urban areas and population growth.